Clinical Study of Antimicrobial Efficacy of Laser Ablation Therapy with Indocyanine Green in Root Canal Treatment - Leonardo, Renato de Toledo [UNESP]; Puente, Carlos García; Berbert, Fabio Luiz Camargo Villela [UNESP]; Faria, Gisele [UNESP]; Nishiyama, Celso Kenji; Orosco, Fernando Accorsi; Rodrigues, Gladiston William Lobo [UNESP]; Ribeiro, Ana Paula Fernandes [UNESP]; Cintra, Luciano Tavares Angelo [UNESP]; Trope, Martin (Elsevier, 2023)
Introduction: Laser ablation (LA) therapy is used as an adjunct to endodontic treatment to improve microbial reduction. However, studies evaluating the impact of LA with indocyanine green (ICG) are scarce. This study aimed to evaluate the antimicrobial efficacy of LA therapy with ICG in root canal treatment. Methods: Sixty patients with periapical lesions in teeth with a single canal and absence of pain, edema, and previous treatment were selected. Patients were randomly allocated into 3 groups according to the apical sizes used (n = 20); 25/04, 30/04, and 35/04 were the final sizes used. In half the patients of each group, 2.5% sodium hypochlorite was used as an irrigating solution, and in the other half, saline solution was used. After instrumentation, all patients received LA therapy with ICG. Root canal sampling was performed before (S1) and after (S2) root canal instrumentation and immediately after LA therapy with ICG (S3). Colony-forming units were counted, and statistical tests were applied (P <.05). Results: There was a significant reduction in colony-forming units from S1 to S2 in all treatment protocols (P <.05); 2.5% sodium hypochlorite as an irrigating solution showed a greater microbial reduction compared with saline solution (P <.05). LA therapy with ICG further reduced the microbial counts significantly (S2 to S3 and S1 to S3) whether sodium hypochlorite or saline was used (P <.05). Conclusions: LA therapy with ICG significantly increased microbial reduction in root canals regardless of instrumentation sizes or the irrigation solution used.
Keywords: Diode laser; laser ablation; photochemotherapies; root canal treatment